Боевая эвтаназия: [роман ] / С. В. Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2021)
Экземпляры: Селтинская районная библиотека (аб) (20210429) / Инвентарный номер: 207754 / Цена: 50 / Авт.знак: С 17 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6